CONTEMPORARY PRACTICES OF INDIRECT WRITTEN FEEDBACK IN HIGH SCHOOL CONTEXT - Widyasari, Yessi; Perdani, Yella Dezas; Rahmi, Gita (Journal of Language and Literature, 2021)
Indirect written feedback is crucial to be conducted since errors are unavoidable in the process of writing. However, many studies have been undertaken in university contexts. Thus, this qualitative case study was carried out to examine a teacher's indirect written feedback practices in senior high school context. The data were obtained from observations, document analysis, and semi-structured interviews through purposive sampling. The findings revealed that coded feedback was mainly used, supplemented by uncoded feedback and commentary. These imply that the coding system is effective in guiding the students to be problem solvers and independent writers. However, the teacher's inconsistency in giving codes emerged because of the use of a large number of codes. Thus, it is suggested to reduce the number of codes and provide sufficient activity to increase students' understanding of the codes. The results of the study are significant to help teachers adjust appropriate methods to teach writing. The results also give long-term benefits for the development of students' writing ability. For further research, it is important to analyze the effect of indirect written feedback strategies on the students' revisions as well as students' preferences on these strategies.